The Elimination of the Paper Mark as Standard of Value - Kuczynski, R. R. (Quarterly Journal of Economics, 1923)
Journal Article The Elimination of the Paper Mark As Standard of Value Get access R. R. Kuczynski R. R. Kuczynski Berlin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 37, Issue 4, August 1923, Pages 761–769, https://doi.org/10.2307/1884061 Published: 01 August 1923